Azo bond formation on metal surfaces. Issue 3 (11th December 2020) - Meng, Xiangzhi; Klaasen, Henning; Viergutz, Lena; Schulze Lammers, Bertram; Witteler, Melanie C.; Mönig, Harry; Amirjalayer, Saeed; Liu, Lacheng; Neugebauer, Johannes; Gao, Hong‐Ying; Studer, Armido; Fuchs, Harald
Abstract: The formation of azo compounds via redox cross‐coupling of nitroarenes and arylamines, challenging in solution phase chemistry, is achieved by on‐surface chemistry. Reaction products are analyzed with a cryogenic scanning tunneling microscope (STM) and X‐ray photoelectron spectroscopy (XPS). By using well‐designed precursors containing both an amino and a nitro functionality, azo polymers are prepared on surface via highly efficient nitro‐amino cross‐coupling. Experiments conducted on other substrates and surface orientations reveal that the metal surface has a significant effect on the reaction efficiency. The reaction was further found to proceed from partially oxidized/reduced precursors in dimerization reactions, shedding light on the mechanism that was studied by DFT calculations. Abstract : Herein we disclose the on‐surface redox coupling of arylamines and nitroarenes on Ag(111). Starting from well‐designed monomeric precursors, the cross‐coupling yielding azo bridged polyphenylenes was investigated by STM and XPS. Further, first steps toward copolymerization were performed with two comonomers. Mechanistic studies and supportive DFT calculations are provided.